Virtual Creature Morphology ‐ A Review. (4th June 2021) - Lai, G.; Leymarie, F.F.; Latham, W.; Arita, T.; Suzuki, R.
Abstract: We present a review of methods for procedurally generating the morphology of virtual creatures. We include a range of methods, with the main groups being from ALife over art to video games. Even though at times these groups overlap, for clarity we have kept this distinction. By including the word virtual, we mean that we focus on methods for simulation in silico, and not physical robots. We also include a historical perspective, with information on methods such as cellular automata, L‐systems and a focus on earlier pioneers in the field.